Profile of Student Learning Motivation in Limited Offline Learning Natural Science Subject - Dewi Ayu Mulyani; Septi Budi Sartika (Scientiae Educatia: Jurnal Pendidikan Sains)
Learning motivation is one of the most important things students must have in supporting learning success. This study aims to describe male and female students' learning motivation profiles in limited offline learning of science subjects. This research uses qualitative methods of a phenomenological approach. The subjects of this study were one male student and one female student in grade IX of SMP Muhammadiyah 4 Porong. Data collection techniques use observation, questionnaires, and interviews. The results of this study show that the learning motivation profile of male students in limited offline learning in science subjects is relatively good by achieving five indicators of learning motivation in limited offline learning. The learning motivation profile of female students in limited offline learning of science subjects is classified as very good by achieving all indicators of learning motivation in limited offline learning. This study concludes that students' learning motivation in offline learning is limited to science subjects is relatively good. Female students have better motivation to learn in offline learning than male students, which may be due to intrinsic motivational factors; female students are better than male students, while other factors are due to student behavior.